Legal Protection for Child Criminals in the Indonesian Justice System - Setyawan, Setyawan; Endah Wahyuningsih, Sri (UNISSULA Semarang, 2025)
Abstract. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System stipulates that juvenile justice in absolute competence is within the scope of the General Court. The form of providing legal protection is intended to provide oportunities for children to become responsible human beings in their future. The objectives of this study: 1). to determine and analyze legal protection for child perpetrators of criminal acts in the current judicial system in Indonesia; 2). to determine and analyze the weaknesses and solutions for legal protection for child perpetrators of criminal acts in the current judicial system in Indonesia. This study uses a normative legal aproach, with a descriptive analytical research method. The data used are primary and secondary data that will be analyzed qualitatively. Research problems are analyzed using the theory of punishment, retributive theory, legal purpose theory, combined theory and legal system theory. The results of the study concluded that: 1) Legal protection for children in the criminal justice system in Indonesia can be seen from the entire legal process, starting from the investigation stage, arrest and detention, prosecution, trial and guidance. The entire process must be carried out based on the provisions of the SPA Law and must prioritize the needs, development and growth of children, both mentally, physically, and socially, and the interests of the community. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPA Law) provides legal protection for children in conflict with the law (consisting of children in conflict with the law, children who are victims of criminal acts and children who are witnesses to criminal acts) in Indonesia.; 2). The weaknesses of legal protection for children who commit crimes are the lack of quality and quantity of human resources of law enforcement officers who handle criminal cases committed by children, and the lack of coordination between law enforcement officers and related institutions that handle criminal cases. The solution to these weaknesses is that law enforcers should improve the quality and quantity of human resources of law enforcement officers who handle criminal cases committed by children and increase synergy between related law enforcers.